A Cross‐linked Conjugated Polymer Photosensitizer Enables Efficient Sunlight‐Induced Photooxidation. Issue 10 (17th January 2019) - Wu, Wenbo; Xu, Shidang; Qi, Guobin; Zhu, Han; Hu, Fang; Liu, Zitong; Zhang, Deqing; Liu, Bin
Abstract: Photooxidation under sunlight has potential in organic synthesis, bacterial killing, and organic waste treatment. Photosensitizers (PSs) can play an important role in this process. High 1 O2 generation efficiency and excellent photostability under sunlight, as well as easy recyclability are ideal properties for PSs, but are not easy to achieve simultaneously. Herein, a pure organic porous conjugated polymer PS, CPTF, shows great photostability, large specific surface area, and high 1 O2 generation efficiency under sunlight for photooxidation. For the oxidation of aromatic aldehyde to aromatic acid, the PS catalyst shows excellent recyclability, and enables solvent‐free reactions in high yields both under direct sunlight and simulated AM 1.5G irradiation. In addition, the successful application of CPTF as an antibacterial agent and organic waste decomposition under simulated AM 1.5G irradiation indicates the potential of CPTF in sunlight‐induced waste water treatment. Abstract : A sunny outlook : A cross‐linked porous conjugated polymer photosensitizer CPTF is used for sunlight‐induced photooxidation. Under simulated AM 1.5G irradiation, benzaldehyde can be oxidized to benzoic acid easily on a 10 g scale in the presence of CPTF. In addition, CPTF can also be used as photocatalyst for sunlight‐induced organic waste decomposition and an antibacterial agent in water.